2018
DOI: 10.3390/ijms19113317
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Transporter Monocarboxylate Transporter 4 Induces Bone Pain in Head and Neck Squamous Cell Carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) poses a significant challenge clinically, as it can invade facial bones and cause bone pain that is undertreated and poorly understood. Here we studied HNSCC bone pain (HNSCC-BP) in an intratibial mouse xenograft model that uses a human HNSCC cell line (SAS cells). These mice develop HNSCC-BP associated with an upregulation of phosphorylated ERK1/2 (pERK1/2), which is a molecular indicator of neuron excitation in the dorsal root ganglia (DRGs) of sensory nerve cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The 4T1 BC cells (1 × 10 5 cells/10 μl) were inoculated in the bone marrow cavity of right tibiae of 4 to 6-week-old female BALB/c mice (4T1 mice) (Harlan Laboratories, Indianapolis, IN), under general anesthesia with ketamine (Ketaset; 90–150 mg/kg, ip) and xylazine (AnaSed; 5–10 mg/kg, ip) as we described [21] . Sham surgery control mice were injected intratibially with PBS.…”
Section: Methods Smentioning
confidence: 99%
“…The 4T1 BC cells (1 × 10 5 cells/10 μl) were inoculated in the bone marrow cavity of right tibiae of 4 to 6-week-old female BALB/c mice (4T1 mice) (Harlan Laboratories, Indianapolis, IN), under general anesthesia with ketamine (Ketaset; 90–150 mg/kg, ip) and xylazine (AnaSed; 5–10 mg/kg, ip) as we described [21] . Sham surgery control mice were injected intratibially with PBS.…”
Section: Methods Smentioning
confidence: 99%
“…The results of this study and previous studies indicate that MCTs transfer lactate from astrocytes to neurons that are involved in the initiation and sustained of inflammatory and neuropathic pain. Furthermore, another study indicated that head and neck squamous cell carcinoma induces an acidic bone microenvironment and leads to bone pain via the lactate transporter MCT 4 42. Thus, the collected evidence reveals that MCTs are involved in pathological processes in some pain states, and it also supports the astrocyte–neurone lactate shuttle hypothesis of pain mechanisms.…”
Section: Discussionmentioning
confidence: 55%
“…Cancer cells produce large amounts of lactate resulting from the Warburg effect ( 28 ) and actively secrete it via the lactate transporter MCT4 ( 13 ) to avoid cell death due to intracellular lactate acidosis. Secreted lactate is then taken up by neighboring cells, such as stromal, endothelial and immune cells, in the tumor microenvironment via the lactate transporter MCT1 as an energy source ( 29 ).…”
Section: Discussionmentioning
confidence: 99%